2017
DOI: 10.1007/s11356-017-9898-0
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase and heat shock protein 70 response in larval brain tissue of Lymantria dispar L. (Lepidoptera, Limantriidae) upon chronic exposure to benzo(a)pyrene

Abstract: The effects of different concentrations of benzo(a)pyrene (BaP) (2, 10, 20, 100, 200, and 2000 ng/g dry food weight) on the activity of acetylcholinesterase (AChE) and concentration of heat-shock protein 70 (hsp70) in fifth instar Lymantria dispar brain tissue were investigated. Inhibition of AChE is a general effect biomarker at the individual level. We observed the most efficient inhibition of this enzyme at medium and high BaP concentrations (20, 100, 200, and 2000 ng/g dry food weight). Western blot analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In insects, it was found that the exposure to stressors leads to a decrease in the synthesis rate of most proteins, but HSP expression increases (Augustyniak et al, 2009;Chapuis et al, 2011). Several types of research enlisted HSPs in evaluating the toxic potential of different stressors in insects, particularly heavy metals (Ahamed et al, 2010;Augustyniak et al, 2009;Ilijin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In insects, it was found that the exposure to stressors leads to a decrease in the synthesis rate of most proteins, but HSP expression increases (Augustyniak et al, 2009;Chapuis et al, 2011). Several types of research enlisted HSPs in evaluating the toxic potential of different stressors in insects, particularly heavy metals (Ahamed et al, 2010;Augustyniak et al, 2009;Ilijin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of B[a]P present in host plant species for L. dispar larvae used in our experiment probably were not high enough to influence brain AChE activity in any way. Ilijin et al [50] found that B[a]P present in low concentrations of 2 and 10 ng/g DW in insect diet did not provoke changes in AChE activity of L. dispar larvae from an unpolluted population, and neither did dietary intake of another PAH, fluoranthene, at low and high concentrations (6.7, 33,5 and 67 ng/g DW) [51].…”
Section: Discussionmentioning
confidence: 99%
“…This type of behavior was observed by Dinan et al [57] during fluoranthene treatment of Drosophila melanogaster cells. Ilijin et al [50] reported that among six tested dietary doses of B[a]P, the largest induction of Hsp70 expression was under the chronic influence of the lowest (2 and 10 ng/g DW) B[a]P concentration. An analogous situation was described in the research of Mrdaković et al [51], where the lowest concentration of fluoranthene (6.7 ng/g DW) caused the greatest elevation of Hsp70 in the brain of L. dispar larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, the exposure to stressors leads to a decrease in the rate of synthesis of most proteins, but Hsp expression increases [ 26 , 27 ]. Several studies have implicated heat shock proteins (Hsps) in evaluating the toxic potential of different stressors in insects, particularly of heavy metals [ 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%